Characterization of Macrophage-Like Cells in Retinal Vein Occlusion Using En Face Optical Coherence Tomography - Zeng, Yunkao; Zhang, Xiongze; Mi, Lan; Gan, Yuhong; Su, Yongyue; Li, Miaoling; Yang, Ruijun; Zhang, Yining; Wen, Feng (Frontiers in Immunology, 2022)
Purpose. To investigate the clinical features of macrophage-like cell (MLC) obtained by en face optical coherence tomography (OCT) in retinal vein occlusion (RVO). Methods. The study involved 36 patients with treatment-naïve unilateral acute RVO, including 21 branch RVO (BRVO) and 15 central RVO. Vessel density, macular thickness was quantified using OCT angiography. A 3μm en face OCT slab on inner limiting membrane in optic nerve head (ONH) region or macular region was used to visualize the MLCs. The MLCs were binarized and quantified using a semiautomated method. The unaffected fellow eyes served as the control group. Results. The morphology of MLCs appeared relatively larger and plumper in RVO eyes. The mean MLC density in ONH and macular region was 2.46 times and 2.86 times higher than their fellow eyes, respectively (p<0.001). The macular MLC density of the occlusive region was significantly lower than the unaffected region in BRVO (p=0.01). The ONH and macular MLC density in nonperfused region were significantly lower than the perfused region in all RVO eyes (p<0.001). ONH MLC density in RVO eyes was negatively correlated with radial peripapillary capillary vessel density (r=-0.413, p=0.012). Both ONH and macular MLC density were positively corelated with macular thickness (r=0.505, p=0.002; r=0.385, p=0.02, respectively). Conclusion. The increased density and changes of morphology characterized by OCT may indicate generalized activation and aggregation of MLCs in RVO. More MLCs are recruited in the perfused region rather than the nonperfused region. RVO eyes with higher density of MLCs tend to suffer thicker macula.